2021
DOI: 10.3390/su13147791
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microencapsulated Organic Acid and Their Salts on Growth Performance, Immunity, and Disease Resistance of Pacific White Shrimp Litopenaeus vannamei

Abstract: Use of antibiotics and other chemicals to combat disease outbreaks has been a bottleneck for the sustainable growth of shrimp industry. Among various replacements proposed, organic acid (OA) and their salts (OS) are commonly used by farmers and feed millers. However, in free forms, their requirement is very high (2–3 kg/MT) as they tend to disassociate before reaching the hindgut. The dosage can be reduced by microencapsulation of the ingredients. In this study, a 63-day trial was conducted to assess the effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…Alkaline phosphatase (ALP) is poly-functional enzyme that plays a vital role in the membrane transport activities, mineralization of the skeleton of aquatic organisms (Zikic et al, 2001), growth, and protein synthesis (Ram and Sathyanesan, 1985). Administration of dietary encapsulated organic acid significantly increased ALP level in the serum of Pacific White Shrimp (Litopenaeus vannamei) compared to the control group (Chowdhury et al, 2021). In the present study, the liver ALP level increased significantly in the SP dietary groups.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Alkaline phosphatase (ALP) is poly-functional enzyme that plays a vital role in the membrane transport activities, mineralization of the skeleton of aquatic organisms (Zikic et al, 2001), growth, and protein synthesis (Ram and Sathyanesan, 1985). Administration of dietary encapsulated organic acid significantly increased ALP level in the serum of Pacific White Shrimp (Litopenaeus vannamei) compared to the control group (Chowdhury et al, 2021). In the present study, the liver ALP level increased significantly in the SP dietary groups.…”
Section: Discussionsupporting
confidence: 48%
“…Several studies have attributed the improvement of nutrient utilization and growth performance of aquatic animals fed on diets containing organic acids and their salts. These compounds also lower digestion pH (Chowdhury et al, 2021), changes the microbial population of the intestinal tract (Ng and Koh, 2016), stimulate digestive enzyme secretion (Chowdhury et al, 2021), and increase feed intake (Da Silva et al, 2015;Omosowone et al, 2018). Omosowone et al (2018) showed that Clarias gariepinus and Oreochromis niloticus fingerlings fed a 2% butyric acid-supplemented diet for 12 weeks had better feed utilization and growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) is known as a polyfunctional enzyme that possess a vital role in the membrane transport activities, mineralization of the skeleton of aquatic organisms (Zikic et al, 2001), growth and synthesis of protein (Ram and Sathyanesan, 1985). Administration of dietary encapsulated organic acid signi cantly increased ALP level in the serum of Paci c White Shrimp (Litopenaeus vannamei) compared to the control group (Chowdhury et al, 2021). In the present study, the liver ALP level increased signi cantly in the SP dietary groups.…”
Section: Discussionsupporting
confidence: 47%
“…Feeding the African cichlid ngerlings with SP-supplemented diets at level of 5 g Kg −1 of dry diet for 56 days resulted in enhancement of growth performance including nal weight, WG, SGR(%), DGI and FCR. Several studies have attributed the improvement of nutrient utilization and growth performance of aquatic animals fed on diets containing organic acids and their salts to reduction of the digesta pH (Chowdhury et al, 2021), changes in microbial population of the intestinal tract (Ng and Koh, 2016), stimulation of digestive enzyme secretion (Chowdhury et al, 2021) and increased feed intake (Da Silva et al, 2015;Omosowone et al, 2018). Omosowone et al (2018) showed that Clarias gariepinus and Oreochromis niloticus ngerlings fed 2% butyric acid-supplemented diet for 12 weeks had better feed utilization and growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…Microencapsulation has become one of the most popular and practical approaches to deliver bioactive compounds to specific regions of the gastro-intestinal tract in farmed animals, e.g., swine [32,33]. A hydrogenated-fat based microencapsulation technique, as described in Chowdhury et al [34], was used in this study to protect the blend of organic acids and essential oils as well as release it into the intestine.…”
Section: Introductionmentioning
confidence: 99%